The location and identity of the Baixos da Judia: Portuguese historical cartography of the Mozambique Channel and its relevance to the wreck of the Santiago in 1585 - Stuckenberg, B. R. (Southern African Humanities, 2021)
The Age of Discoveries produced a wealth of Portuguese literature. One of its especially notable components is the collection of shipwreck narratives assembled by B. Gomes de Brito (1735-6) under the title História Trágico-Marítima. Of this compilation the British historian C.R. Boxer has written: «There can be no two opinions about the historical value of the História Trágico-Marítima. Written almost invariably with the utmost frankness, these narratives bring vividly before us the dangers and discomforts of life aboard the crowded East-India carracks.» Discoveries of Portuguese shipwreck sites in the South African region during recent decades have given new impact and historical significance to several of these narratives. Objects from the ships, personal possessions of the passengers and crew, coins from the Royal Treasury, and relics of the cargoes that were sought in the East Indies at such high cost to the Portuguese nation, provide tangible links with those maritime dramas. Staff of the Natal Museum have been associated with research on three of the wrecks: the São João of 1552, the São Bento of 1554, and the Santiago of 1585.